Opinion of Croatian consumers on traditional Dalmatian lamb in the process of obtaining a PDO label - Martić Kuran, Linda; Drinovac Topalović, Marijana; Đugum, Jelena; Krvavica, Marina (2021)
The protection of Dalmatian lamb ("Dalmatinska janjetina") with a protected designation of origin label (PDO) is based on the specific quality of meat of Dalmatian pramenka lamb and the traditional lamb breeding method in the geographic area that coincides with the breeding area of Dalmatian pramenka (indigenous Croatian sheep breed). Under the name of "Dalmatinska janjetina", only the meat of lambs of Dalmatian pramenka, bred exclusively in Dalmatia, can be placed on the market. In the process of obtaining a PDO label, which has recently been completed at the Croatian national level and is currently in the process at the EU level, a survey among Croatian consumers (a sample of 1,034 consumers from all over Croatia) was conducted to determine the recognition of this product on the Croatian market, as well as consumer preferences considering similar products from other Croatian regions. The research has shown that Croatian consumers recognize Dalmatian lamb as a traditional, high-quality product. Thus, almost 75 % of the respondents recognize it as a particular type of lamb of better quality than others on the Croatian market. Almost 85 % of the respondents use lamb regardless of type in their diet, but more than 58 % always on special occasions (folk festivals and family celebrations), especially if prepared in the traditional way (lamb on a spit) by which Dalmatia as a region is recognized by more than 85 % of the respondents. The market reputation and connection with the geographic production area are why Croatian consumers rather buy Dalmatian lamb over others.
Zaštita "Dalmatinske janjetine” zaštićenom oznakom izvornosti (ZOI) temelji se na specifičnoj kvaliteti mesa i tradicionalnom načinu uzgoja janjadi dalmatinske pramenke na geografskom području koje se poklapa s uzgojnim područjem izvorne hrvatske pasmine ovaca, Dalmatinske pramenke. Pod nazivom "Dalmatinska janjetina" na tržište se može staviti samo meso janjadi dalmatinske pramenke, uzgojene isključivo u Dalmaciji. U zakonskom postupku registracije zaštićene oznake ZOI, koji je nedavno završen na hrvatskoj nacionalnoj razini, a trenutno je u tijeku postupak na razini EU-a, provedeno je istraživanje među hrvatskim potrošačima na uzorku od 1.034 potrošača s područja čitave Hrvatske, kako bi se utvrdila prepoznatljivost ovog proizvoda na hrvatskom tržištu, kao i preferencije potrošača s obzirom na slične proizvode iz drugih hrvatskih regija. Istraživanje je pokazalo da hrvatski potrošači prepoznaju „Dalmatinsku janjetinu“ kao tradicionalni, visokokvalitetni proizvod. Gotovo 75 % ispitanika “Dalmatinsku janjetinu” prepoznaje kao posebnu vrstu janjetine kvalitetniju od ostalih vrsta janjetine na hrvatskom tržištu. Gotovo 85 % ispitanika koristi janjetinu u prehrani, ali više od 58 % samo u posebnim prilikama (narodne svetkovine i obiteljska slavlja), osobito ako se priprema pečenjem na ražnju. Navedeni tradicionalni način pripreme janjetine pečenjem na ražnju više od 85 % ispitanika povezuje s Dalmacijom kao regijom.
Der Schutz von „Dalmatinischem Lamm“ mit dem Herkunftsschutzzeichen (kroat. Abk. ZOI) beruht auf der spezifischen Fleischqualität und der traditionellen Art der Zucht von Lämmern des dalmatinischen Schafs Pramenka auf dem geographischen Gebiet, das mit dem Zuchtgebiet der originellen kroatischen Schafsrasse, Dalmatinischer Pramenka, überlappt. Unter der Bezeichnung „Dalmatinisches Lamm“ kann man lediglich das Lammfleisch der Dalmatinischen Schafsrasse Pramenka auf den Markt bringen, die ausschließlich in Dalmatien gezüchtet wurde. Im gesetzlichen Verfahren zur Registrierung des Herkunftsschutzzeichens (ZOI), das auf der kroatischen Nationalebene vor kurzem abgeschlossen wurde, wobei das Verfahren zurzeit auf der EU-Ebene anhängig ist, wurde eine Forschung unter den kroatischen Herstellern an einem Muster von 1.034 Verbrauchern aus ganz Kroatien durchgeführt, um die Erkennbarkeit dieses Produkts auf dem kroatischen Markt sowie die Präferenzen der Verbraucher unter Berücksichtigung ähnlicher Produkte aus anderen kroatischen Gebieten festzustellen. Diese Forschung ergab, dass die kroatischen Verbraucher das „Dalmatinische Lamm“ als traditionelles, qualitativ hochwertiges Produkt erkennen. Beinahe 75 % der Befragten erkennen das „Dalmatinische Lamm“ als eine besondere Art von Lamm, die im Vergleich zu den anderen auf dem kroatischen Markt vorhandenen Arten von Lamm weitaus qualitativ hochwertiger ist. Beinahe 85 % der Befragten nutzt das Lammfleisch in der Ernährung, aber mehr als 58 % nutzt es lediglich zu besonderen Zwecken (bei Volksfesten und Familienfeiern), insbesondere, wenn man es als ein ganzes Lamm am Spieß nutzt. Die soeben erwähnte traditionelle Art der Zubereitung von Lamm durch Braten des ganzen Lamms am Spieß verbindet mehr als 85 % der Befragten mit Dalmatien als Gebiet.
La protección de la carne de cordero de Dalmacia con la Denominación de Origen Protegida (DOP) está basada en la calidad específica de la carne y la forma tradicional de criar corderos de la raza pramenka de Dalmacia en una zona geográfica que coincide con la zona de cría de la raza ovina originaria de Croacia: pramenka de Dalmacia. Bajo el nombre de carne de cordero de Dalmacia, sólo se puede comercializar la carne de cordero de pramenka de Dalmacia, criado exclusivamente en Dalmacia. En el proceso de solicitud de la marca protegida DOP, completado recientemente a nivel nacional croata y que actualmente está en proceso a nivel de la UE, fue realizada la encuesta de opinión del consumidores croatas sobre una muestra de 1034 consumidores de toda Croacia, para determinar si este producto está reconocible en el mercado Croata, así como las preferencias de los consumidores con respecto a productos similares de otras regiones croatas. La investigación mostró que los consumidores croatas reconocen la carne de cordero de Dalmacia como un producto tradicional de alta calidad. Casi el 75 % de los encuestados reconoce la carne de cordero de Dalmacia como un tipo especial de carne de cordero de mejor calidad que otros tipos de cordero en el mercado croata. Casi el 85 % de los encuestados usa la carne de cordero en su dieta, pero más del 58 % solo en ocasiones especiales (festivales folclóricos y celebraciones familiares), especialmente si se prepara a la parrilla. Más del 85 % de los encuestados asocian esta forma tradicional de preparar la carne de cordero con asado a la parrilla con Dalmacia como región. La reputación en el mercado y la conexión con la zona geográfica de producción (Dalmacia) son las razones por las que los consumidores croatas prefieren comprar la carne de cordero de Dalmacia que otros tipos de carne de cordero.
La tutela della carne d’agnello dalmata (“Dalmatinska janjetina”) con il marchio DOP (denominazione di origine protetta) si basa sulla specifica qualità della carne e sulle modalità dell’allevamento tradizionale degli agnelli di razza pramenka dalmata sull’area geografica che coincide con la regione d’allevamento della razza ovina autoctona croata della pramenka dalmata. Con la denominazione di “Dalmatinska janjetina”, cioè, può essere commercializzata sul mercato soltanto la carne degli agnelli di razza pramenka dalmata allevati esclusivamente in Dalmazia. In seno alla procedura legislativa di registrazione del marchio protetto DOP, recentemente conclusosi in Croazia a livello nazionale, e che è attualmente in corso a livello dell’UE, è stato condotto un sondaggio d’opinione tra i consumatori croati su un campione di 1.034 soggetti originari di ogni parte della Croazia, al fine di accertare la riconoscibilità di questo prodotto sul mercato domestico, oltre alle preferenze dei consumatori rispetto a prodotti simili provenienti da altre regioni croate. Il sondaggio ha evidenziato che i consumatori croati riconoscono la carne d’agnello dalmata (“Dalmatinska janjetina”) come prodotto tradizionale e di gran qualità. Quasi il 75 % degli intervistati ha riconosciuto la “Dalmatinska janjetina” come un particolare tipo di carne d’agnello, migliore dal punto di vista qualitativo rispetto agli altri tipi di carne d’agnello presenti sul mercato croato. Quasi l’85 % degli intervistati fa uso della carne d’agnello nella propria alimentazione, ma poco più del 58 % soltanto in speciali occasioni (festività nazionali e celebrazioni in ambiente familiare), in particolare se arrostita allo spiedo. Questa tradizionale tecnica di cottura allo spiedo è associata da oltre l’85 % degli intervistati alla Dalmazia come entità regionale.
Bibliografija: 27 jed.
Abstract ; Zusammenfassung ; Sažetak ; Riassunto ; Resumen.
Keywords: Dalmatinska janjetina -- Oznaka izvornosti -- Mišljenje potrošača